M2 macrophage inhibits the antitumor effects of Lenvatinib on intrahepatic cholangiocarcinoma - Yang, Long; Han, Pinsheng; Cui, Tao; Miao, Yu; Zhao, Tianyu; Cui, Zilin; Chen, Yijia; Chi, Hao; Zhang, Jieying; Zhang, Yamin (Frontiers in Immunology, 2023)
The relationship between the tumor microenvironment and the network of key signaling pathways in cancer plays a key role in the occurrence and development of tumors. Tumor-associated macrophages (TAMs) are important inflammatory cells in the tumor microenvironment and play an important role in tumorigenesis and progression. Macrophages in malignant tumors, mainly the M2 subtype, promote tumor progression by producing cytokines and down-regulating anti-inflammatory immune responses. Several articles have investigated the effect of macrophages on the sensitivity of cancer chemotherapeutic agents, but few such articles have been reported in cholangiocarcinoma, so we investigated the effect of M2 macrophage on the sensitivity of cholangiocarcinoma cells to Lenvatinib compared to M1.Methods: THP-1 monocytes were polarized to M0 macrophage by phorbol 12-myristate 13-acetate (PMA) and then induced to differentiate into M1 and M2 macrophages by LPS, IFN-γ and IL-4 and IL-13, respectively. Macrophages and cholangiocarcinoma cells were co-cultured prior to 24 hours of Lenvatinib administration, cancer cell apoptosis was detected by western-blot, FACS analysis of Annexin V and PI staining. Furthermore, we use xCELLigence RTCA SP Instrument (ACEA Biosciences) to monitor cell viability of Lenvatinib administration in co-culture of cholangiocarcinoma cells and macrophages. After tumorigenesis in immunodeficient mice, Lenvatinib was administered, and the effects of M2 on biological characteristics of cholangiocarcinoma cells were investigated by immuno-histochemistry.Results: mRNA and protein expression of M1 and M2 markers confirmed the polarization of THP-1 derived macrophages, which provided a successful and efficient model of monocyte polarization to TAMs. Lenvatinib-induced apoptosis of cholangiocarcinoma cells was significantly reduced when co-cultured with M2 macrophage, whereas apoptosis of cholangiocarcinoma cells co-cultured with M1 macrophage was increased. In the CDX model, Lenvatinib-induced cancer cell apoptosis was markedly reduced, and proliferative cells increased in the presence of M2 macrophages.Angiogenesis related factors was significantly increased in cholangiocarcinoma cells co-cultured with M2.Conclusions: Compared with M1, M2 macrophages can inhibit the anti-tumor effect of Lenvatinib on cholangiocarcinoma through immune regulation, which may be related to the tumor angiogenesis factor effect of M2 macrophage.